Cytogenetic study of pathogenomics of Aspergillus niger on the freshwater host fish Oriochromis niloticus - Ghosh, Subarna; Bandyopadhyay, Probir Kumar (Bangladesh Journal of Zoology, 2023)
Infected fresh water Tilapia Oreochromis niloticus, were brought alive from Canning fisheries and aquatic resource, Canning, India to parasitology laboratory, Department of Zoology for pathogenic examination. Macroscopic production of infection observed and the specimen was isolated and characterized on the basis of morphological and molecular analysis. The species was identified as Aspergillus niger. The effect of this pathogenic fungus on host physiology was observed by monitoring changes in biochemical, histological parameters. Native polyacrylamide gel electrophoresis have been used to analyze malate dehydrogenase (MDH), acid phosphatase (Acph) and peroxidase (Px) isoenzymes in different tissues (liver, kidney, muscle and heart) of the host fish in order to study the tissue specificity of these isoenzymes. The percentage amount of MDH in general varied significantly between muscle and different studied tissues. Peroxidase isoenzyme was recorded in liver and heart only with significant increase in liver. The cumulative mortalities of the intraperitoneal infection increased along with the sporangiospore concentrations; the highest mortality observed was 70% with108 CFU as compared to the control. Bangladesh J. Zool. 51(1): 99-117, 2023